Signaling New Product Reliability with After-Sales Service Contracts - Bakshi, Nitin; Kim, Sang-Hyun; Savva, Nicos (Management Science, 2015)
Prior studies on performance-based contracting (PBC) for after-sales services have highlighted its advantages over traditional resource-based contracting (RBC), when products are established and their reliability is known to all parties. We develop a game theoretic model to investigate how these insights are affected when the vendor is privately informed about the reliability of a newly developed product. A novel feature of our model is the interaction between reliability signaling (private information) and the vendor’s discretionary investment in spares inventory (private action), which arises naturally in the setting we consider. We find that this interaction leads to contrasting equilibrium outcomes under the two contracts: RBC induces the vendor to focus on inventory savings, leading to underinvestment in spares, whereas PBC induces the vendor to focus on reliability signaling, achieved through overinvestment in inventory. As a result, neither contract is efficient. We investigate two means to mitigate this inefficiency, but either approach has caveats: (a) making inventory verifiable removes the trade-off between reliability signaling and inventory investment, but results in diverging contract preferences between the vendor and the buyer; (b) pooling inventories across multiple buyers saves inventory costs but it also hinders reliability signaling, potentially exacerbating inefficiency. This paper was accepted by Yossi Aviv, operations management.